Ankle taping: support given by different materials. Issue 4 (December 1989) - Capasso, G; Maffulli, N; Testa, V
Abstract : Three different adhesive and two non-adhesive tapes were used by three operators to assess the compressive action exerted on the ankle at the moment of strapping, during different phases of gait, and after some days of treatment in ten volunteers. Only the adhesive tapes were still able to prevent swelling after five days. They should be used if a prolonged compressive action is required.